PCARD platform for mHealth monitoring - Depolli, Matjaž (Informatica, 2016)
The introduction of information and communication technologies (ICT) into the integrated healthcare system could increase the self-management of health and therefore increase the efficacy and decrease the costs of overall health management. A personal mobile health monitoring system (PCARD) has been developed, which uses moderately-priced and user-friendly technological solutions, e.g. wireless body sensors for data acquisition, advanced algorithms for data analysis, widely available smart phones for visualization of measurements, and the existing communication infrastructure for data transfer. The solution is unobtrusive, works with existing devices, and provides useful information to both direct users and to the health care system. The PCARD system starts with measurement of ECG signal that incorporates significant information about the global health state. It then continues with display of the signal and its analysis on a personal terminal, such as smartphone and on Cloud-based storage, processing, and visualization software. Four pilot studies have been designed to validate to which extent the continuous measured ECG data could contribute to improved quality and efficiency of the healthcare. Also, the level of safety and reliability, the acceptance from users, and the potential for commercialization will be validated in the scope of the pilots.